Asphalt modifier containing polyethylene and asphalt mixture prepared therefrom

By adding polyethylene and other ingredients to the asphalt modifier, a new type of asphalt modifier was prepared, which solved the problems of improved performance and resource shortage of asphalt additives in the prior art, and realized the preparation of high-performance asphalt mixtures, reducing production costs and environmental pollution.

CN119432106BActive Publication Date: 2025-05-06HEBEI PROVINCIAL COMM PLANNING & DESIGN INST
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510030999.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-05-06
Estimated Expiration
2045-01-09

AI Technical Summary

Technical Problem

In the prior art, there is still room for improvement in the physical performance indicators and rut resistance of asphalt additives, and traditional asphalt resources face the dual challenges of shortage and environmental pollution.

Method used

The asphalt modifier containing polyethylene is used, and the preparation method includes mixing coal liquefied asphalt and pretreated glue powder, adding solubilizer and plasticizer, and then adding matrix asphalt and polyethylene, and preparing the modifier after high-speed shearing and extrusion granulation.

Benefits of technology

The road performance of asphalt mixture has been significantly improved, including the improvement of dynamic modulus and dynamic stability, the use of petroleum asphalt has been reduced, the preparation process has been simplified, and pollution-free production has been achieved, and production costs have been reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention relates to the technical field of road asphalt modification, specifically to an asphalt modifier containing polyethylene and an asphalt mixture prepared therefrom. The asphalt modifier containing polyethylene includes the following weight components: 8-15 parts of matrix asphalt, 30-50 parts of coal liquefaction asphalt, 30-50 parts of pretreated rubber powder, 1-4 parts of solubilizer, 1-4 parts of plasticizer, and 2-4 parts of waste polyethylene plastic. The asphalt modifier containing polyethylene also includes weight component A: 0.3-3.0 parts of modified basalt fiber. The present invention prepares an asphalt modifier containing polyethylene through a mixing process. Compared with traditional modifiers, the basic raw materials of the present invention are completely derived from solid waste resources, which not only realizes the resource utilization of waste, but also simplifies the preparation process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of road asphalt modification, in particular to an asphalt modifier containing polyethylene and an asphalt mixture prepared therefrom. Background Art

[0002] Asphalt pavement is widely used in Chinese cities, but such pavement is often damaged in a short period of time due to various diseases. Therefore, improving the performance of asphalt to extend the life of the pavement has become a key task that needs to be solved in the field of road engineering. At the same time, with the rapid development of the economy, the consumption of natural resources is increasing, which requires that while improving the pavement conditions, the optimization of the energy structure must be taken into account to achieve the goals of environmental protection, resource conservation and sustainable development.

[0003] Patent CN104073003A proposes a road asphalt modifier and a preparation method thereof, aiming to improve the performance of traditional modifiers. The preparation method comprises mixing coal, waste tire slices and catalytic cracking oil slurry in a precisely measured mass ratio, adding a coal liquefaction catalyst metal element, and reacting at a temperature of 350°C to 450°C for 1 to 6 hours to obtain a road modifier. However, the high temperature reaction conditions and complex catalytic cracking oil slurry preparation process of this method lead to high production costs.

[0004] Chinese invention patent 200610012547.9 discloses a method of using coal liquefaction residue as a road asphalt modifier. When preparing modified asphalt, the coal liquefaction residue modifier accounts for 5% to 10% of the total weight of the modified asphalt. This method is simple and effectively utilizes coal liquefaction residue. However, due to the limited amount of addition, when the content of coal liquefaction residue is further increased, the asphalt will become brittle and the low-temperature performance will decrease, making it difficult to meet the performance requirements for road use.

[0005] Patent 201010198795.3 discloses a method for preparing an anti-rutting agent for asphalt concrete pavement from coal direct liquefaction residue. The method involves crushing the coal direct liquefaction residue, petroleum asphalt and polyethylene respectively, mixing them in a certain proportion, and finally preparing an anti-rutting agent in the form of solid particles of 2-5 mm through an extrusion granulation process. This anti-rutting agent can significantly improve the anti-rutting performance of asphalt pavement, but it still has limitations because it uses petroleum asphalt as a raw material and cannot improve other properties of asphalt concrete.

[0006] In the existing technology, there is still room for further improvement in the physical performance indicators and anti-rutting performance of asphalt additives. At the same time, traditional asphalt resources face the dual challenges of shortage and environmental pollution.

[0007] Therefore, we propose an asphalt modifier containing polyethylene and an asphalt mixture prepared therefrom. Summary of the invention

[0008] The object of the present invention is to provide an asphalt modifier containing polyethylene and an asphalt mixture prepared therefrom, so as to solve the problems raised in the prior art.

[0009] To achieve the above object, the present invention provides the following technical solutions:

[0010] A method for preparing an asphalt modifier containing polyethylene comprises the following steps:

[0011] Mix the coal liquefied asphalt and pretreated rubber powder evenly, add solubilizer and plasticizer, stir at 150-180°C for 1-2 hours, then add base asphalt and polyethylene, continue stirring for 1-2 hours, send into a high-speed shearing machine for shearing to obtain a mixture; extrude the mixture into granules to obtain an asphalt modifier containing polyethylene.

[0012] Furthermore, the polyethylene-containing asphalt modifier comprises the following components by weight: 5-20 parts of base asphalt, 20-60 parts of coal liquefaction asphalt, 20-60 parts of pretreated rubber powder, 0-5 parts of solubilizer, 0-5 parts of plasticizer, and 1-5 parts of waste polyethylene plastic.

[0013] Furthermore, the polyethylene-containing asphalt modifier comprises the following components by weight: 8-15 parts of base asphalt, 30-50 parts of coal liquefaction asphalt, 30-50 parts of pretreated rubber powder, 1-4 parts of solubilizer, 1-4 parts of plasticizer, and 2-4 parts of waste polyethylene plastic.

[0014] Furthermore, the matrix asphalt is one of 70# road petroleum asphalt and 90# road petroleum asphalt, preferably 70# road petroleum asphalt.

[0015] Furthermore, the asphaltene content in the coal liquefaction asphalt is 60-85wt%, and the relative content of C and H elements is 70-90%.

[0016] Furthermore, the coal liquefaction pitch has an ash content of 1-15wt%, a softening point of 160-180°C, a mass change of 0.01-0.1%, and is in powder form.

[0017] In the above technical solution, coal liquefaction pitch is the main by-product of coal liquefaction, and its yield is about 30% of the raw coal.

[0018] Furthermore, the preparation method of the pretreated rubber powder is as follows:

[0019] The waste tire rubber powder, softener and activator are mixed at 80-120° C. for 10-30 minutes, added into a twin-screw extruder, the reaction temperature is controlled at 180-210° C., the rotation speed is 100-200 rpm, and the pretreated rubber powder is obtained by extrusion granulation.

[0020] Furthermore, the mass ratio of the waste tire rubber powder, the softener and the activator is 1: (0.02-0.2): (0.01-0.05).

[0021] Furthermore, the Mooney viscosity of the pretreated rubber powder is 20-40M, the ash content is 3-8%, the carbon black content is 28-48%, and the rubber hydrocarbon content is 48-65%.

[0022] In the above technical solution, the CS bonds in the waste tire rubber powder particles are broken to complete the desulfurization, and under the action of the large shear force during the desulfurization process, various filler systems in the waste tire rubber powder are destroyed, which promotes its adsorption and infiltration with the matrix asphalt.

[0023] Furthermore, the solubilizer is one or more of phthalates, epoxy compounds, cycloalkane oil, aliphatic hydrocarbon oil, aromatic oil, turpentine oil, pine tar oil, and tung oil.

[0024] Furthermore, the plasticizer is one or more of aliphatic dibasic acid esters, phthalic acid esters, phthalic acid esters, terephthalic acid esters, benzene polyesters, benzoic acid esters, and polyol esters.

[0025] Furthermore, the waste polyethylene plastic is one or more of high-density polyethylene (HDPE) and low-density polyethylene (LDPE).

[0026] Furthermore, the shearing process conditions are: shearing rate 3000-7000 r / min, shearing temperature 150-190° C., and shearing time 1-2 h.

[0027] Furthermore, the polyethylene-containing asphalt modifier also includes weight component A: 0.3-3.0 parts of modified basalt fiber.

[0028] Furthermore, the preparation method of the modified basalt fiber is as follows:

[0029] Step (1): uniformly mix basalt fiber, anhydrous ethanol, deionized water and 3-aminopropyltriethoxysilane, react at 55-65° C. for 4-6 hours, and obtain amino basalt fiber after filtering, washing and drying;

[0030] Step (2): Under nitrogen protection, dendrobium phenol, epichlorohydrin and benzyltriethylammonium chloride are mixed uniformly, reacted at 80-90°C for 3-5h, cooled to 50-55°C, sodium hydroxide solution is added, and the reaction is continued for 2-3h. After filtering, washing and drying, dendrobium phenol diglycidyl ether is obtained;

[0031] Step (3): the amino-modified basalt fiber, p-aminodiphenylamine and tetrahydrofuran are mixed evenly, dendrobium phenol diglycidyl ether is added, the mixture is reacted at 50-60° C. for 12-24 hours, nitrogen is introduced, terminal isocyanate polybutadiene and dibutyltin dilaurate are added, the mixture is mixed evenly, the mixture is reacted at 70-80° C. for 3-5 hours, the mixture is cooled to room temperature, filtered, washed and dried to obtain modified basalt fiber.

[0032] In the above technical scheme, the surface of basalt fiber is modified by 3-aminopropyltriethoxysilane (KH550) to obtain amino basalt fiber; then, dendrobium phenol, a natural plant extract, is used as a raw material to react with epichlorohydrin to obtain epoxidized dendrobium phenol containing two epoxy groups; dendrobium phenol diglycidyl ether is used as a cross-linking agent, and the epoxy groups at both ends respectively undergo ring-opening reactions with the amino groups on the surface of the amino basalt fiber and the amino groups of p-aminodiphenylamine, thereby grafting the antioxidant to the surface of the basalt fiber, thereby achieving the loading and fixation of the antioxidant; at the same time, hydroxyl groups are generated during the ring-opening reaction of amino and epoxy groups, and continue to react with the isocyanate group of terminal isocyanate polybutadiene to obtain modified basalt fiber.

[0033] Furthermore, in the step (1), the mass ratio of basalt fiber to anhydrous ethanol, deionized water, and 3-aminopropyltrimethoxysilane is 1:(10-12):(2-4):(0.3-0.5).

[0034] Furthermore, in step (2), the mass ratio of dendrobium phenol, epichlorohydrin, benzyltriethylammonium chloride and sodium hydroxide solution is 1:(2-3):(0.05-0.08):(0.5-1.0), and the concentration of the sodium hydroxide solution is 30-40wt%.

[0035] Furthermore, in the step (3), the mass ratio of the amino basalt fiber, p-aminodiphenylamine, tetrahydrofuran and dendrobium phenol diglycidyl ether is 1: (0.5-1.5): (15-20): (0.4-1.2).

[0036] Furthermore, in the step (3), the amount of the isocyanate-terminated polybutadiene is 50-150% of the mass of the amino-treated basalt fiber.

[0037] Furthermore, in step (3), the amount of dibutyltin dilaurate used is 0.1-0.3% of the mass of the amino basalt fiber.

[0038] An application of an asphalt modifier containing polyethylene comprises the following steps:

[0039] Step S1: mixing the asphalt modifier containing polyethylene and the base asphalt at 180° C. to obtain a composite modified asphalt;

[0040] Step S2: Mix the coarse aggregate and the fine aggregate for 60 seconds, then add the composite modified asphalt and mix for 90 seconds, and finally add the mineral powder and mix for 90 seconds. The mixing temperature is 162-166° C. to obtain an asphalt mixture.

[0041] Furthermore, the composite modified asphalt includes the following components by weight: 4 parts of an asphalt modifier containing polyethylene and 6 parts of a base asphalt.

[0042] Furthermore, the coarse aggregate is composed of 10-15 mm crushed stone and 5-10 mm crushed stone in a mass ratio of 40:30.

[0043] Furthermore, the fine aggregate is machine-made sand.

[0044] Furthermore, the asphalt mixture includes the following components by weight: 70 parts of coarse aggregate, 24 parts of machine-made sand, 6 parts of mineral powder, and 6 parts of composite modified asphalt.

[0045] Compared with the prior art, the present invention has the following beneficial effects:

[0046] 1. The present invention discloses an asphalt modifier containing polyethylene and an asphalt mixture prepared therefrom, and a petroleum asphalt modifier is prepared by a mixing process. Compared with traditional modifiers, the basic raw materials of the present invention are completely derived from solid waste resources, which not only realizes the resource utilization of waste, but also simplifies the preparation process. The composite modifier significantly improves the road performance of the asphalt mixture, especially increases the dynamic modulus of the asphalt mixture to more than 15000MPa, and the dynamic stability also reaches more than 8000 times / mm. During the preparation process, the compatibility between coal liquefaction asphalt and petroleum asphalt is improved by adding a compatibilizer and a plasticizer, further improving the modification effect. The present invention basically realizes pollution-free production and effectively reduces potential harm to the human body. Using coal liquefaction asphalt and pretreated rubber powder as the basic raw materials, a variety of organic compounds are integrated, the utilization rate of solid waste resources is greatly improved, 30%-40% of the amount of petroleum asphalt raw materials can be saved, and the cost is much lower than SBS modified asphalt, thereby significantly reducing the production cost. In addition, the modifier prepared by the present invention is flexible in use. It can be used to modify the base asphalt first and then produce the asphalt mixture; it can also be added directly during the mixing process of the base asphalt and stone, which simplifies the operation process.

[0047] 2. An asphalt modifier containing polyethylene and an asphalt mixture prepared by the present invention, wherein basalt fiber is surface modified by 3-aminopropyltriethoxysilane (KH550) to obtain amino basalt fiber; dendrobium phenol is a natural plant extract with significant antioxidant properties, which can effectively remove free radicals and slow down the occurrence of oxidation reactions; dendrobium phenol is used as a raw material to react with epichlorohydrin to obtain epoxidized dendrobium phenol containing two epoxy groups; dendrobium phenol diglycidyl ether is used as a crosslinking agent The epoxy groups at both ends of the basalt fiber react with the amino groups on the surface of the amino basalt fiber and the amino groups of p-aminodiphenylamine to form a ring-opening reaction, thereby grafting the antioxidant to the surface of the basalt fiber, realizing the loading and fixation of the antioxidant, and further improving the material's anti-aging and durability; at the same time, the hydroxyl groups generated in the process of the amino and epoxy ring-opening reaction continue to react with the isocyanate group of the terminal isocyanate polybutadiene to form a new chemical bond, improve the adhesion between the basalt fiber and the matrix, and obtain modified basalt fiber. Applying it to the preparation process of asphalt can not only enhance the mechanical properties and high temperature resistance of asphalt, but also improve its crack resistance, anti-aging ability, improve fluidity and construction properties, thereby extending the service life of the material. DETAILED DESCRIPTION

[0048] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0049] In this embodiment, the matrix asphalt is 70# road petroleum asphalt; coal liquefaction asphalt: from China Shenhua Coal to Oil Chemical Co., Ltd. of the State Energy Group; waste tire rubber powder: particle size is 30-80 mesh, from Shijiazhuang Zhongshi Hengda Mineral Products Co., Ltd.; solubilizer: aromatic oil, model SD-30, from Shandong Xinjiu New Materials Technology Co., Ltd.; plasticizer: terephthalate; waste polyethylene plastic: low-density polyethylene, from Shandong Laizhou Fushide New Materials Technology Co., Ltd.; basalt fiber: length 6mm, single fiber diameter 15μm, sourced from Tai'an Songze Composite Materials Co., Ltd.; terminal isocyanate polybutadiene: brand TP-1001, sourced from Jiangshan Chemical (Shanghai) Co., Ltd.; softener: cyclohexane oil, model KN4006; activator: dibenzothiazole disulfide; 10-15mm gravel and 5-10mm gravel: diabase gravel, sourced from Hubei Huancai Red Stone Co., Ltd.; machine-made sand: specification is 0-5mm, sourced from Lingshou County Yongzhuo Mineral Products Co., Ltd.; mineral powder: grade s95.

[0050] In the following examples and comparative examples, 1 portion is equal to 20 g.

[0051] The preparation method of the pre-treated rubber powder used in this embodiment is as follows:

[0052] The waste tire rubber powder, softener and activator were mixed at 100°C for 20 minutes, added into a twin-screw extruder, the reaction temperature was controlled at 200°C, the rotation speed was 150rpm, and the pretreated rubber powder was obtained by extrusion granulation; the mass ratio of the waste tire rubber powder, softener and activator was 1:0.1:0.02.

[0053] Example 1: An asphalt modifier containing polyethylene, comprising the following process:

[0054] 20 parts of coal liquefaction asphalt and 20 parts of pretreated rubber powder were mixed evenly, 0.5 parts of solubilizer and 1 part of plasticizer were added, and stirred at 150°C for 1 hour, and then 5 parts of base asphalt and 1 part of waste polyethylene plastic were added, and the mixture was stirred for 1 hour, and then sent to a high-speed shearing machine for shearing (shear rate 3000r / min, shear temperature 150°C, shear time 1 hour) to obtain a mixture; the mixture was extruded and granulated to obtain an asphalt modifier containing polyethylene;

[0055] An application of an asphalt modifier containing polyethylene comprises the following steps:

[0056] Step S1: 4 parts of an asphalt modifier containing polyethylene and 6 parts of a base asphalt are mixed uniformly at 180° C. to obtain a composite modified asphalt;

[0057] Step S2: 70 parts of coarse aggregate (composed of 10-15 mm crushed stone and 5-10 mm crushed stone in a mass ratio of 40:30) and 24 parts of machine-made sand are mixed for 60 seconds, and then 6 parts of composite modified asphalt are added and mixed for 90 seconds, and finally 6 parts of mineral powder are added and mixed for 90 seconds, and the mixing temperature is 163°C to obtain an asphalt mixture.

[0058] Embodiment 2: An asphalt modifier containing polyethylene, comprising the following process:

[0059] 40 parts of coal liquefaction asphalt and 40 parts of pretreated rubber powder were mixed evenly, 2 parts of solubilizer and 3 parts of plasticizer were added, and the mixture was stirred at 160°C for 1.5 hours, and then 10 parts of base asphalt and 2 parts of waste polyethylene plastic were added, and the mixture was stirred for 1.5 hours, and then the mixture was sent to a high-speed shearing machine for shearing (shear rate 4000r / min, shear temperature 170°C, shear time 1.5 hours) to obtain a mixture; the mixture was extruded and granulated to obtain an asphalt modifier containing polyethylene;

[0060] An application of an asphalt modifier containing polyethylene comprises the following steps:

[0061] Step S1: 4 parts of an asphalt modifier containing polyethylene and 6 parts of a base asphalt are mixed uniformly at 180° C. to obtain a composite modified asphalt;

[0062] Step S2: 70 parts of coarse aggregate (composed of 10-15 mm crushed stone and 5-10 mm crushed stone in a mass ratio of 40:30) and 24 parts of machine-made sand are mixed for 60 seconds, and then 6 parts of composite modified asphalt are added and mixed for 90 seconds, and finally 6 parts of mineral powder are added and mixed for 90 seconds, and the mixing temperature is 166°C to obtain an asphalt mixture.

[0063] Embodiment 3: An asphalt modifier containing polyethylene, comprising the following process:

[0064] Mix 50 parts of coal liquefaction asphalt and 50 parts of pretreated rubber powder evenly, add 4 parts of solubilizer and 4 parts of plasticizer, stir at 170°C for 2 hours, then add 15 parts of base asphalt and 4 parts of waste polyethylene plastics, continue stirring for 2 hours, and send into a high-speed shearing machine for shearing (shear rate 6000r / min, shear temperature 180°C, shear time 2h) to obtain a mixture; extrude the mixture into granules to obtain an asphalt modifier containing polyethylene; the other steps are the same as Example 1.

[0065] Embodiment 4: An asphalt modifier containing polyethylene, comprising the following process:

[0066] 60 parts of coal liquefaction asphalt and 60 parts of pretreated rubber powder were mixed evenly, 5 parts of solubilizer and 5 parts of plasticizer were added, and stirred at 180°C for 2 hours, and then 20 parts of base asphalt and 5 parts of waste polyethylene plastic were added, and stirring was continued for 2 hours, and the mixture was sent to a high-speed shearing machine for shearing (shear rate 7000r / min, shear temperature 190°C, shear time 2h) to obtain a mixture; the mixture was extruded and granulated to obtain an asphalt modifier containing polyethylene;

[0067] An application of an asphalt modifier containing polyethylene comprises the following steps:

[0068] Step S1: 4 parts of an asphalt modifier containing polyethylene and 6 parts of a base asphalt are mixed uniformly at 180° C. to obtain a composite modified asphalt;

[0069] Step S2: 70 parts of coarse aggregate (composed of 10-15 mm crushed stone and 5-10 mm crushed stone in a mass ratio of 40:30) and 24 parts of machine-made sand are mixed for 60 seconds, and then 6 parts of composite modified asphalt are added and mixed for 90 seconds, and finally 6 parts of mineral powder are added and mixed for 90 seconds, and the mixing temperature is 162°C to obtain an asphalt mixture.

[0070] Embodiment 5: An asphalt modifier containing polyethylene, comprising the following process:

[0071] 50 parts of coal liquefaction asphalt and 50 parts of pretreated rubber powder were mixed evenly, 4 parts of solubilizer, 4 parts of plasticizer and 1 part of modified basalt fiber were added, and stirred at 170°C for 2 hours, and then 15 parts of base asphalt and 4 parts of waste polyethylene plastic were added, and stirring was continued for 2 hours, and the mixture was sent to a high-speed shearing machine for shearing (shear rate 6000r / min, shear temperature 180°C, shear time 2h) to obtain a mixture; the mixture was extruded and granulated to obtain an asphalt modifier containing polyethylene;

[0072] The preparation method of modified basalt fiber is as follows:

[0073] Step (1): 2 parts of basalt fiber, 22 parts of anhydrous ethanol, 6 parts of deionized water, and 0.8 parts of 3-aminopropyltriethoxysilane are mixed evenly, reacted at 60° C. for 5 hours, filtered, washed, and dried to obtain amino basalt fiber;

[0074] Step (2): Under nitrogen protection, 2 parts of dendrobium phenol, 5 parts of epichlorohydrin and 0.12 parts of benzyltriethylammonium chloride are mixed evenly, reacted at 85°C for 4 hours, cooled to 52°C, 1.6 parts of 35wt% sodium hydroxide solution are added, and the reaction is continued for 2.5 hours. After filtering, washing and drying, dendrobium phenol diglycidyl ether is obtained;

[0075] Step (3): 2 parts of amino basalt fiber, 2 parts of p-aminodiphenylamine and 36 parts of tetrahydrofuran are mixed evenly, 1.6 parts of dendrobium phenol diglycidyl ether are added, the mixture is reacted at 55° C. for 18 h, nitrogen is introduced, 2 parts of isocyanate-terminated polybutadiene and 0.004 parts of dibutyltin dilaurate are added, the mixture is mixed evenly, the mixture is reacted at 75° C. for 4 h, the mixture is cooled to room temperature, filtered, washed and dried to obtain modified basalt fiber; the other steps are the same as those in Example 3.

[0076] Embodiment 6: An asphalt modifier containing polyethylene, comprising the following process:

[0077] 50 parts of coal liquefaction asphalt and 50 parts of pretreated rubber powder were mixed evenly, 4 parts of solubilizer, 4 parts of plasticizer and 0.3 parts of modified basalt fiber were added, and stirred at 170°C for 2 hours, and then 15 parts of base asphalt and 4 parts of waste polyethylene plastic were added, and the stirring was continued for 2 hours, and the mixture was sent to a high-speed shearing machine for shearing (shear rate 6000r / min, shear temperature 180°C, shear time 2h) to obtain a mixture; the mixture was extruded and granulated to obtain an asphalt modifier containing polyethylene;

[0078] The preparation method of modified basalt fiber is as follows:

[0079] Step (1): 0.3 parts of basalt fiber, 3 parts of anhydrous ethanol, 0.6 parts of deionized water, and 0.09 parts of 3-aminopropyltriethoxysilane are mixed evenly, reacted at 55° C. for 4 hours, filtered, washed, and dried to obtain amino basalt fiber;

[0080] Step (2): Under nitrogen protection, 0.2 parts of dendrobium phenol, 0.4 parts of epichlorohydrin and 0.01 parts of benzyltriethylammonium chloride are mixed evenly, reacted at 80°C for 3 hours, cooled to 50°C, 0.1 parts of 30wt% sodium hydroxide solution are added, and the reaction is continued for 2 hours. After filtering, washing and drying, dendrobium phenol diglycidyl ether is obtained;

[0081] Step (3): 0.3 parts of amino basalt fiber, 0.15 parts of p-aminodiphenylamine and 4.5 parts of tetrahydrofuran are mixed evenly, 0.12 parts of dendrobium phenol diglycidyl ether are added, the mixture is reacted at 50° C. for 12 hours, nitrogen is introduced, 0.15 parts of isocyanate-terminated polybutadiene and 0.0003 parts of dibutyltin dilaurate are added, the mixture is mixed evenly, the mixture is reacted at 70° C. for 3 hours, the mixture is cooled to room temperature, filtered, washed and dried to obtain modified basalt fiber; the other steps are the same as those in Example 3.

[0082] Embodiment 7: An asphalt modifier containing polyethylene, comprising the following process:

[0083] 50 parts of coal liquefaction asphalt and 50 parts of pretreated rubber powder were mixed evenly, 4 parts of solubilizer, 4 parts of plasticizer and 3 parts of modified basalt fiber were added, and stirred at 170°C for 2 hours, and then 15 parts of base asphalt and 4 parts of waste polyethylene plastic were added, and the stirring was continued for 2 hours, and the mixture was sent to a high-speed shearing machine for shearing (shear rate 6000r / min, shear temperature 180°C, shear time 2h) to obtain a mixture; the mixture was extruded and granulated to obtain an asphalt modifier containing polyethylene;

[0084] The preparation method of modified basalt fiber is as follows:

[0085] Step (1): 5 parts of basalt fiber, 60 parts of anhydrous ethanol, 20 parts of deionized water, and 2.5 parts of 3-aminopropyltriethoxysilane are mixed evenly, reacted at 65° C. for 6 hours, filtered, washed, and dried to obtain amino basalt fiber;

[0086] Step (2): Under nitrogen protection, 6 parts of dendrobium phenol, 18 parts of epichlorohydrin and 0.48 parts of benzyltriethylammonium chloride are mixed evenly, reacted at 90°C for 5 hours, cooled to 55°C, 6 parts of 40wt% sodium hydroxide solution are added, and the reaction is continued for 3 hours. After filtering, washing and drying, dendrobium phenol diglycidyl ether is obtained;

[0087] Step (3): 5 parts of amino basalt fiber, 7.5 parts of p-aminodiphenylamine and 100 parts of tetrahydrofuran were mixed evenly, 6 parts of dendrobium phenol diglycidyl ether were added, and the mixture was reacted at 60°C for 24 hours, nitrogen was introduced, 7.5 parts of isocyanate-terminated polybutadiene and 0.015 parts of dibutyltin dilaurate were added, the mixture was mixed evenly, and the mixture was reacted at 80°C for 5 hours. The mixture was cooled to room temperature, filtered, washed and dried to obtain modified basalt fiber. The other steps were the same as those in Example 3.

[0088] Comparative Example 1: An asphalt modifier containing polyethylene, comprising the following process:

[0089] Compared with Example 5, the modified basalt fiber in Comparative Example 1 is replaced with basalt fiber of the same mass, and the other steps are the same as those in Example 5.

[0090] experiment:

[0091] Experiment 1: 40g of the composite modified asphalt obtained in Examples 1-7 and Comparative Example 1 were taken to prepare samples, and ordinary rubber asphalt (rubber modified asphalt with 20% rubber powder content produced by Hebei Jiaoke Material Technology Co., Ltd.) was used as a control group, and the performances thereof were tested and the test results were recorded:

[0092] Referring to methods T0606-2011, T0605-2011 and T0604-2011 in the Test Procedure for Asphalt and Asphalt Mixtures in Highway Engineering (JTG E20-2011), the softening point, 5°C elongation and 25°C penetration of the samples were tested respectively, and the data were recorded.

[0093] The viscosity was tested by a rotational viscometer at a test temperature of 180°C.

[0094] Asphalt aging test: Put the asphalt sample to be tested into a weighing dish with a mass of 50±0.5g, form an asphalt film with uniform thickness, put it into a film heating test box, and heat it in the oven and maintain it at 163℃±1℃. Keep it for 5 hours, take out the sample, and evaluate the aging performance of the sample by calculating the penetration ratio, residual ductility and mass change index.

[0095] The test results are shown in Table 1:

[0096] Table 1 Various properties of composite modified asphalt and ordinary rubber asphalt in Examples 1-7 and Comparative Example 1

[0097]

[0098] According to the data in Table 1, the following conclusions can be clearly drawn:

[0099] Compared with the control group, the penetration, ductility and 180°C viscosity of the composite modified asphalt samples prepared in Examples 1-7 were all reduced, and the softening point and anti-aging performance were significantly improved, indicating that the composite modified asphalt prepared by the present invention has significantly improved high-temperature performance compared with ordinary rubber asphalt; although the low-temperature ductility is reduced, this is mainly due to the high asphaltene and ash content in the coal liquefaction asphalt, but through the adjustment of solubilizers and plasticizers, the various indicators of the modified asphalt are still maintained within the product standard range. At the same time, the composite modified asphalt prepared by the present invention is superior in construction and workability, which helps to reduce the mixing temperature, thereby achieving the effect of energy saving and emission reduction. In addition, the index parameters of the composite modified asphalt samples prepared in Examples 1-7 before and after aging do not change much, and have more excellent anti-aging performance.

[0100] Compared with Example 5, the penetration, softening point and anti-aging performance of the composite modified asphalt sample prepared in Comparative Example 1 are all reduced, which indicates that compared with basalt fiber, the modified basalt fiber prepared by the present invention can effectively improve the high-temperature stability and anti-aging ability of asphalt, thereby improving the overall performance and durability of asphalt materials.

[0101] Experiment 2: A preparation process of a common rubber asphalt mixture, comprising the following steps: 70 parts of coarse aggregate (composed of 10-15 mm crushed stone and 5-10 mm crushed stone in a mass ratio of 40:30) and 24 parts of machine-made sand are mixed for 60 seconds, then 6 parts of common rubber asphalt are added and mixed for 90 seconds, and finally 6 parts of mineral powder are added and mixed for 90 seconds, the mixing temperature is 180°C, to obtain a common rubber asphalt mixture;

[0102] The asphalt mixtures prepared in Examples 1-7 were used to test various properties of the mixtures, and compared with the properties of ordinary rubber asphalt mixtures. The test results are shown in Table 2.

[0103] Table 2 Properties of asphalt mixtures prepared in Examples 1-7 and common rubber asphalt mixtures

[0104]

[0105] According to the data in Table 2, the following conclusions can be clearly drawn:

[0106] Compared with ordinary rubber asphalt mixture, the dynamic stability and freeze-thaw splitting strength ratio of the asphalt mixture prepared by the asphalt modifier containing polyethylene prepared by the present invention are increased, and its high temperature performance and water stability indicators are significantly better than ordinary rubber asphalt, indicating that the asphalt modifier containing polyethylene prepared by the present invention has a significant effect on the performance improvement of asphalt mixture. The maximum bending tensile strain of the asphalt mixture prepared by Examples 1-4 is lower than that of the comparative example, indicating that the addition of coal liquefaction asphalt modifier has a certain negative impact on the low temperature performance of asphalt mixture. The addition of solubilizer and plasticizer can reduce the influence of coal liquefaction asphalt on the low temperature performance of the mixture. Although it still remains within the required range of the index (>2800με), the addition of coal liquefaction asphalt modifier greatly improves the dynamic modulus of the asphalt mixture and meets the requirement of high modulus asphalt (>14000MPa); at the same time, the addition of modified basalt fiber to the asphalt modifier of Examples 5-7 further improves the maximum bending-tensile strain of the asphalt mixture, greatly enhances the fatigue resistance of the asphalt mixture, enhances the rutting resistance, water damage resistance and durability of the road surface, extends the maintenance cycle and road service life, and has significant social and economic benefits.

[0107] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A method for preparing an asphalt modifier containing polyethylene, characterized in that: The steps include: The coal liquefied asphalt and the pre-treated rubber powder are mixed evenly, a solubilizer and a plasticizer are added, and the mixture is stirred at 150-180°C for 1-2 hours, and then the base asphalt and polyethylene are added, and the mixture is stirred for 1-2 hours, and then the mixture is sent to a high-speed shearing machine for shearing to obtain a mixture; the mixture is extruded and granulated to obtain an asphalt modifier containing polyethylene; The asphalt modifier containing polyethylene comprises the following components by weight: 5-20 parts of base asphalt, 20-60 parts of coal liquefaction asphalt, 20-60 parts of pretreated rubber powder, 0-5 parts of solubilizer, 0-5 parts of plasticizer, 1-5 parts of waste polyethylene plastic; The polyethylene-containing asphalt modifier further comprises component A by weight: 0.3-3.0 parts of modified basalt fiber; The preparation method of the modified basalt fiber is as follows: Step (1): uniformly mix basalt fiber, anhydrous ethanol, deionized water and 3-aminopropyltriethoxysilane, react at 55-65° C. for 4-6 hours, and obtain amino basalt fiber after filtering, washing and drying; Step (2): Under nitrogen protection, dendrobium phenol, epichlorohydrin and benzyltriethylammonium chloride are mixed uniformly, reacted at 80-90°C for 3-5h, cooled to 50-55°C, sodium hydroxide solution is added, and the reaction is continued for 2-3h. After filtering, washing and drying, dendrobium phenol diglycidyl ether is obtained; Step (3): the amino-modified basalt fiber, p-aminodiphenylamine and tetrahydrofuran are mixed evenly, dendrobium phenol diglycidyl ether is added, the mixture is reacted at 50-60° C. for 12-24 hours, nitrogen is introduced, terminal isocyanate polybutadiene and dibutyltin dilaurate are added, the mixture is mixed evenly, the mixture is reacted at 70-80° C. for 3-5 hours, the mixture is cooled to room temperature, filtered, washed and dried to obtain modified basalt fiber.

2. The method for preparing an asphalt modifier containing polyethylene according to claim 1, characterized in that: The matrix asphalt is one of 70# road petroleum asphalt and 90# road petroleum asphalt.

3. The method for preparing an asphalt modifier containing polyethylene according to claim 1, characterized in that: The preparation method of the pretreated rubber powder is as follows: The waste tire rubber powder, softener and activator are mixed at 80-120° C. for 10-30 minutes, added into a twin-screw extruder, the reaction temperature is controlled at 180-210° C., the rotation speed is 100-200 rpm, and the pretreated rubber powder is obtained by extrusion granulation.

4. The method for preparing an asphalt modifier containing polyethylene according to claim 1, characterized in that: The solubilizer is one or more of phthalates, epoxy compounds, cycloalkane oil, aliphatic hydrocarbon oil, aromatic oil, turpentine oil, pine tar oil, and tung oil.

5. The method for preparing an asphalt modifier containing polyethylene according to claim 1, characterized in that: The plasticizer is one or more of aliphatic dibasic acid esters, phthalic acid esters, terephthalic acid esters, benzoic acid esters, and polyol esters.

6. An asphalt modifier containing polyethylene obtained according to the preparation method according to any one of claims 1 to 5.

7. The use of an asphalt modifier containing polyethylene according to claim 6, characterized in that: The following steps are involved: Step S1: mixing the asphalt modifier containing polyethylene and the base asphalt at 180° C. to obtain a composite modified asphalt; Step S2: Mix the coarse aggregate and the fine aggregate for 60 seconds, then add the composite modified asphalt and mix for 90 seconds, and finally add the mineral powder and mix for 90 seconds. The mixing temperature is 162-166° C. to obtain an asphalt mixture.

Citation Information

Patent Citations

  • Road asphalt modifier and utilization method thereof

    CN100439449C

  • Method for preparing bituminous concrete pavement anti-rutting agent from directly-liquefied coal residue

    CN101844892A

  • Road asphalt modifier and preparation method thereof

    CN104073003A

  • Anti-rut agent, composition for preparing anti-rut agent and preparation method of anti-rut agent

    CN104744954A